Propuesta de un conjunto máximo de reacciones químicas independientes para modelar el proceso de gasificación de coque de petróleo - Paniagua Rodríguez, Juan Carlos (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
This work was focused on investigating the linearly independent reactions, thermodynamically feasible, carried out during the gasification process of complex molecules of petroleum coke. Through the methodology called “Generalized Stoichiometry” a system that contains the maximum number of independent chemical reactions to simulate the gasification process was found, which consists of three linearly independent stoichiometric equations: a) partial combustion between of petroleum coke and oxygen; b) oxidation between petroleum coke and carbon dioxide, known as “Boudouard Reaction”; and c) reaction between water and carbon monoxide, known as “Water-Shift reaction”. The simulated process is focused on the prediction of molar flows of the main products (H2,CO,CO2,H2S), which allowed to know the molar advances for three reactions previously mentioned. This simulation was used to compare five types of coke (CK1A, CK1B, CK2A, CK2B and CK3), of different composition and empirical formula, chosen as case studies. In order to explore the flexibility, two operating policies of the gasification process were simulated, engaging CO/CO2 ratios in the range of 20 to 30; this range is reported in the literature as nominal operation. In the first of these policies water supply was changed in decreasing order, maintaining constant oxygen and coke fluxes, the second operating policy considered change of oxygen flow, holding constant steam and coke flows. Later, case gas phase composition was obtained for each simulated type of studied coke, molar fluxes of substances of this phase were added and compared the relative volume of the reactor to carry out the gasification of each type coke, with reference to the volume of the gas phase generated when the lightest coke was gasified (CK3, C36H51.5O85N0.15S1.15A). Finally, it was observed that the relative size of the reactor required to gasify each type of coke follows, qualitatively, the same trend of two parameters, the mass ratio H⁄O and the carbon content, weight %, of each coke. Similarly, the demand for water supply also follows the trend of the carbon content in each coke.

El presente trabajo se enfocó a investigar las reacciones linealmente independientes, termodinámicamente factibles, que se llevan a cabo durante el proceso de gasificación de moléculas complejas de coque de petróleo. Por medio de la metodología llamada “Estequiometria Generalizada” se encontró un sistema que contiene el número máximo de reacciones químicas independientes requeridas para simular el proceso de gasificación, el cual consta de tres ecuaciones estequiométricas linealmente independientes: a) combustión parcial entre el coque y el oxígeno; b) oxidación entre el coque y el dióxido de carbono, conocida como “reacción de Boudouard”; y c) reacción entre agua y monóxido de carbono, conocida como “reacción Water-Shift”. La simulación del proceso se enfocó a la predicción de flujos molares de los productos principales (H2,CO,CO2,H2S), lo que permitió conocer los avances molares de las tres reacciones mencionadas previamente. Esta simulación se utilizó para comparar cinco tipos de coque (CK1A, CK1B, CK2A, CK2B y CK3), de diferente composición y fórmula empírica, elegidos como casos de estudio. A fin de explorar la flexibilidad, se simularon dos políticas de operación del proceso de gasificación, manteniendo relaciones CO/CO2 en el intervalo de 20 a 30; este intervalo se reporta en la literatura como de operación nominal. En la primera de estas políticas se modificó el suministro de agua de forma decreciente, manteniendo constante los flujos de oxígeno y de coque; la segunda política de operación consideró el cambio del flujo de oxígeno, manteniendo constantes los flujos de vapor y de coque.
Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Química
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2012-0058; Reacciones químicas; Gasificación de coque; Petróleo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4825